SEGREGAÇÃO DO ESPAÇO URBANO EM VIANA (ES): ANÁLISE SOBRE OS EFEITOS DA ATIVIDADE IMOBILIÁRIA NO BAIRRO DE VILA BETHÂNIA - Santos, Fernanda Barboza dos (2021)
The work deals with the process of segregation in a portion of the city of Viana (ES), municipality belonging to the Greater Vitória Metropolitan Region (RMGV), through the analysis of space production carried out by the recent strategies of the real estate sector in the neighborhood of Vila Bethânia. The research is constituted as exploratory, of a qualitative nature and the modality refers to the case study. It seeks to understand how new real estate products installed or being installed in the aforementioned neighborhood, they can reflect the current production of the space and what is the impact on the process of segregation. The results achieved allowed a set of conclusions that reveal that the emergence of closed condominium real estate is geared towards residential or industrial use, close to well-consolidated urban facilities, such as BR-101 / BR-262, it seems to show the insertion of new dynamics that collaborate for greater contradictions in the structuring of the urban space in Vienna, as well as complex the process of residential segregation.